EFEKTIVITAS PIJAT MARMET UNTUK MENCEGAH BENDUNGAN ASI SELAMA MENYUSUI: SEBUAH STUDI PRA EKSPERIMEN - Rifa Rahmi; Rika Ruspita (JOMIS (Journal of Midwifery Science), 2025)
ABSTRACT Many mothers experience common complications in breastfeeding. The purpose of this study was to identify the effect of Marmet breast massage on breast milk engorgement. The study was conducted at the Independent Practice of Midwife Rosita. The research method used was a quasi-experiment on postpartum mothers on the first day until the seventh day of postpartum. On the eighth day, observations were made on the occurrence of breast milk engorgement. This study used two groups, namely the intervention group and the control group. The number of samples used was 32 samples. Data analysis used the chi-square test. In this study, it was found that Marmet breast massage on postpartum mothers was not effective for breast milk engorgement. Therefore, it is recommended that even though Marmet breast massage in this study was not significantly effective, education on correct breastfeeding techniques and breast care should still be provided to postpartum mothers. In addition, support from family and health professionals is very important in helping postpartum mothers overcome breastfeeding problems. Practical training and guidance on how to breastfeed, correct baby attachment, and correct breast massage techniques can also increase breastfeeding success and prevent complications such as breast milk engorgement.